Fiscal Performance and Fiscal Implications of the EU Accession in Poland - Ryszard Rapacki (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2005)
This paper seeks to explore the fiscal performance in Poland - one of the top reformer transition economies and simultaneously the largest of ten new EU member countries. At the same time it aims to highlight major fiscal implications of country's accession to the European Union. If not properly addressed, some of these implications or challenges may endanger Poland's fiscal stability and by the same token – adversely affect the speed and smoothness of country's integration process with the European Union. If persisting, they may in the longer run also jeopardize (or at least delay) Poland's membership in the EMU. – – This paper seeks to explore the fiscal performance in Poland - one of the top reformer transition economies and simultaneously the largest of ten new EU member countries. At the same time it aims to highlight major fiscal implications of country's accession to the European Union. If not properly addressed, some of these implications or challenges may endanger Poland's fiscal stability and by the same token – adversely affect the speed and smoothness of country's integration process with the European Union. If persisting, they may in the longer run also jeopardize (or at least delay) Poland's membership in the EMU.
Conference: International Conference on “European Constitution and European Integration”, Taipei, 10-11 November 2005; Additional information: Paper prepared for the international conference on “European Constitution and European Integration”, Taipei, 10-11 November 2005.
Keywords: h3; h5; 330; fiscal performance; eu accession; fiscal performance; european union